Altered Autonomic Function in Individuals at Clinical High Risk for Psychosis - Kocsis, Anna; Gajwani, Ruchika; Gross, Joachim; Gumley, Andrew I.; Lawrie, Stephen M.; Schwannauer, Matthias; Schultze-Lutter, Frauke; Grent-‘t-Jong, Tineke; Uhlhaas, Peter J. (Frontiers in Psychiatry, 2020)
Introduction: Alterations in autonomic functioning in individuals diagnosed with schizophrenia are well documented. Yet, it is currently unclear whether these dysfunctions extend into the clinical high-risk state. Thus, we investigated resting heart rate (RHR) and heart rate variability (HRV) indices in individuals at clinical high-risk for psychosis (CHR-P). Methods: We recruited 117 CHR-P participants, 38 participants with affective disorders and substance abuse (CHR-N) as well as a group of 49 healthy controls. CHR-P status was assessed with the Comprehensive Assessment of At-Risk Mental States (CAARMS) and the Schizophrenia Proneness Instrument, Adult Version (SPI-A). We obtained five minutes, eyes-open resting-state MEG data, which was used for the extraction of cardiac field-related inter-beat-interval data and from which heart-rate and heart-rate variability measures were computed. Results: Compared to both CHR-N and healthy controls, CHR-P participants were characterized by an increased RHR, which was not explained by differences in psychopathological comorbidity and medication status. Increased RHR correlated with the presence of subthreshold psychotic symptoms and associated distress. No differences between groups were found for heart-rate variability measures, however. Conclusion: The current study provides evidence of alterations in autonomic functioning as disclosed by increased RHR in CHR-P participants. Future studies are needed to further evaluate this characteristic feature of CHR-P individuals and its potential predictive value for psychosis development.